The tense superficial state of the discretely fixed surfaces of friction. - Сорокатий, Р.В.; Диха, М.О.; Посонський, С.Ф. (Problems of Tribology, 2015)
Sorokaty R.V., Dykha M.O. Posonsky S.F., The tense superficial state of the discretely fixed surfaces of fric-tion.The calculation analysis of the tense state of the discretely fixed surface is conducted at the different degrees of discreteness and set it optimum values after the criterion of a minimum of tensions in the superficial fixed layer.